2021
DOI: 10.3390/biology10111131
|View full text |Cite
|
Sign up to set email alerts
|

Oxford Nanopore MinION Direct RNA-Seq for Systems Biology

Abstract: Long-read direct RNA sequencing developed by Oxford Nanopore Technologies (ONT) is quickly gaining popularity for transcriptome studies, while fast turnaround time and low cost make it an attractive instrument for clinical applications. There is a growing interest to utilize transcriptome data to unravel activated biological processes responsible for disease progression and response to therapies. This trend is of particular interest for precision medicine which aims at single-patient analysis. Here we evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…It is worth noting that long-read sequencing technology, including sequencing chemistry and basecalling, has improved since the long reads in this analysis were generated. We also ran a similar analysis on a direct RNA ONT dataset generated with newer chemistry (SQK-RNA002) and basecalled with Guppy v5.0.7 [ 13 ]. Just as with the older data, the hybrid-read assembly achieves better accuracy than either the long or the short-read assembly.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that long-read sequencing technology, including sequencing chemistry and basecalling, has improved since the long reads in this analysis were generated. We also ran a similar analysis on a direct RNA ONT dataset generated with newer chemistry (SQK-RNA002) and basecalled with Guppy v5.0.7 [ 13 ]. Just as with the older data, the hybrid-read assembly achieves better accuracy than either the long or the short-read assembly.…”
Section: Resultsmentioning
confidence: 99%
“…A transcript is the next stage after the genome in the transfer of biological information, at which new characteristics appear, such as changes in the number of transcripts encoded by one gene and their expression. In total, about 14,000 genes are expressed in HepG2 cells [ 101 ]. At the transcriptome level for the HepG2 cell line, it has been shown that 50 genes are upregulated in comparison with normal hepatocytes [ 102 ].…”
Section: Comparison Of Hepg2 Normal Hepatocyte Hb and Hccmentioning
confidence: 99%
“…As a result of two transcriptomic profilings at the Institute of Biomedical Chemistry (IBMC), expression data were obtained for the HepG2 cell line in different years (Supplementary File S1, Table S1). The first batch of IBMC data (IBMC.1) is described in Pyatnitskiy et al [6], and the raw data is available from the NCBI SRA repository under study accession number PRJNA765908. The second batch of IBMC data (IBMC.2) was obtained in 2021 (see Sections 4.1-4.3 above), and the raw data is available from the NCBI SRA repository under study accession number PRJNA956723.…”
Section: Resultsmentioning
confidence: 99%